# algebra

(35) I need to determine equation of g(x) that results from translating function
f(x) = x^2 + 3 and upward 7 units

thank you

1. Steve

g(x) = f(x) + 7 = (x^2+3)+7 = x^2+10

## Similar Questions

1. ### algebra

Determine the equation of g(x) that results from translating the function f(x) = x^2 + 9 upward 11 units.
2. ### algebra

please help me determine the equation of g(x) that results from translating the function f(x) = x^2 + 3 upward 7 units
3. ### Math

Determine the equation of g(x) that results from translating the function f(x) = x2 + 5 upward 6 units.
4. ### Math

Determine the equation of g(x) that results from translating the function f(x) = x2 + 5 upward 6 units.
5. ### Algebra

Determine the equation of g(x) that results from translating the function g(x)f(x)=x^2 +3 upward 10 units 1) g(x)=(x+13)^2 2) g(x)= (x+15)^2 3) g(x)= (x+4)^2 -11 4) g(x)= (x+4)^2 +11
6. ### algebra

Determine the equation of g (x) that results from translating the function f(x)=x^2+5 upward 13 units.
7. ### math

Determine the equation of g(x) that results from translating the function f(x) = x^2 + 9 upward 15 units
8. ### math

Determine the equation of g(x) that results from translating the function f(x) = x^2 + 9 upward 15 units
9. ### math

Determine the equation of g(x) that results from translating the function f(x)=x^2+9 upward 15 units. A)g(x)=(x+24)^2 B)g(x)=(x + 15)^2+9 C)g(x)=x^2-6 D)g(x =x^2+24